Writing the Greek Revolution: Harry Mark Petrakis’s The Hour of the Bell - David Roessel (European Journal of American Studies)
Petrakis’s novels about the Greek Revolution are the most significant efforts by an American author, in this case a Greek American author, to place the narrative of the struggle in front of an American public. This paper uses the journal that Petrakis kept while writing The Hour of the Bell to examine his thoughts and motives in the composition of the book, with close attention to Petrakis’s reading of the American philhellene Samuel Gridley Howe’s contemporary history of the war. The ways Petrakis uses Howe, and the ways he does not, offer insight into Petrakis’s own goals and conflicts in writing his version of the Greek Revolution for an American public.